The rise and fall of a population of Hyla boans: Reproduction in a neotropical gladiator frog - Magnusson, William Ernest; Lima, Albertina Pimental; Hero, Jean Marc; Araújo, Maria Carmozina de (Journal of Herpetology, 1999)
A population of Hyla boans was studied in central Amazonian rainforest during 15 years. The species differs from other intensively-studied gladiator frogs, Hyla rosenbergi and Hyla faber, in that males reach larger sizes than females, most reproduction is in the dry season, males call mainly from trees and rarely from nest basins, and most nest basins have aquatic connections to streams. Many adults (15% of females, 21% of males) were captured over more than one breeding season, and some were captured over five breeding seasons. Sizes of juveniles, and growth of one individual indicate that males require at least two years between hatching and entering the breeding population. Daily calling was bimodal, with peaks after dusk and before dawn. Rainfall reduced calling activity during the peak of the breeding season. The population at the site declined to zero density after nine years of study and the site still had not been recolonized six years later. The exponential rate of decline of the population (-0.58) was more than three times the exponential rate of increase (0.15) at the beginning of the study.
Keywords: Anura; Hyla; Hyla Boans; Hyla Rosenbergi; Vertebrata